2006
DOI: 10.1016/j.elecom.2006.06.012
|View full text |Cite
|
Sign up to set email alerts
|

High rate capability of carbon nanofilaments with platelet structure as anode materials for lithium ion batteries

Abstract: Carbon nanofilaments (CNFs) with platelet structure have been prepared by liquid phase carbonization using porous anodic alumina template, and their lithium ion insertion/extraction properties have been examined as a function of heat treatment temperature and filament diameter. The CNFs heat-treated at 1000°C reveal higher capacitance and higher rate capability compared with those heat-treated at higher temperatures. Further, it is found that higher reversible capacity is obtained for the CNFs with reduced dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 16 publications
3
56
0
Order By: Relevance
“…It is well known that the electrochemical properties of lithium-ion batteries strongly depend on the synthetic conditions, such as starting materials, test temperatures, lengths of times, and cooling rate [3]. To improve the capability of batteries to get high power density, utilization of nanostructured materials with small particle size and large surface area is considered, in order to reduce diffusion distance of ions [1,2], including to increase electrochemical activity and charge/discharge efficiency [4]. It was demonstrated that the rate capabilities of nanostructured electrodes were improved, comparing to their bulk counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the electrochemical properties of lithium-ion batteries strongly depend on the synthetic conditions, such as starting materials, test temperatures, lengths of times, and cooling rate [3]. To improve the capability of batteries to get high power density, utilization of nanostructured materials with small particle size and large surface area is considered, in order to reduce diffusion distance of ions [1,2], including to increase electrochemical activity and charge/discharge efficiency [4]. It was demonstrated that the rate capabilities of nanostructured electrodes were improved, comparing to their bulk counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium ion batteries are used in a wide range of portable electronic devices, including mobile phones, laptop computers, and video cameras [1,2]. It is well known that the electrochemical properties of lithium-ion batteries strongly depend on the synthetic conditions, such as starting materials, test temperatures, lengths of times, and cooling rate [3].…”
Section: Introductionmentioning
confidence: 99%
“…We would like to point out that for example, research on novel high rate capable anodes is well under way and cells with LTO [19,20] can already sustain very high charge rate up to 80C. While LTO may not be the ideal anode material due to its high voltage, other high rate anodes [21][22][23] are to be developed as a result of the increasing research activity in this field. Hence, batteries that can be charged at very high rate are not as impossible as implied by ZGMJ, but they may require a significant shift in the materials and cell design used in current Li-ion technology.…”
Section: ) High Charge/discharge Ratementioning
confidence: 99%
“…intercalates into the Li 4 Ti 5 O 12 , while the carbon in the Li 4 Ti 5 O 12 will also react with Li ? ions [29,30]. The latter reaction would lead to an irreversible capacity included in the discharge capacity.…”
Section: Electrochemical Characterizationmentioning
confidence: 97%